IMPROVEMENT OF MATHEMATICS LEARNING OUTCOMES ABOUT DISTANCE, TIME, AND SPEED THROUGH PROJECT BASED LEARNING (PjBL) MODEL TO FIFTH GRADE STUDENTS OF SD NEGERI KLEDUNGKRADENAN IN ACADEMIC YEAR OF 2020/2021 - Irfan Fadilah; Wahyudi Wahyudi; Tri Saptuti Susiani (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
AbstractThe objectives of the study were: (1) to describe the steps in implementing Project Based Learning (PjBL) model in improving mathematics learning outcomes about distance, time, and speed, (2) to increase mathematics learning outcomes about distance, time and speed by applying Project Based Learning (PjBL), and (3) to describe the constraints and solutions in implementing Project Based Learning (PjBL) model in improving mathematics learning outcomes about distance, time, and speed. The research was collaborative classroom action research conducted in three cycles. The subjects were students and teacher of fifth grade SDN Kledungkradenan. The data were qualitative and quantitative data. Data collection techniques used observation, interviews, and tests. The data validity used triangulation of techniques and triangulation of sources. Quantitative and qualitative data analysis included data reduction, presentation, and conclusion. The results showed that: (1) the steps in the implementation of Project Based Learning (PjBL) model were: (a) presenting problems, (b) preparing project plans, (c) preparing project activity schedules, (d) monitoring project implementation, (e) presenting project results, (f) evaluating project results; (2) the application of Project Based Learning (PjBL) model improved mathematics learning outcomes about distance, time and speed; (3) the constrains were: some students were passive in project activities and did not get enough tools needed in making projects while the solutions were: the teacher monitored the learning and discussion activities, the teacher encouraged the students to participate actively in project activities, and the teacher and the students prepared the tools and materials needed in learning